TRANSFORMASI GIZI BALITA STUNTING: PENGARUH BISKUIT TINGGI PROTEIN BERBASIS WHEY PROTEIN TERHADAP KADAR SCFA - Adhimah, Ayu Fauziyyah; Afifah, Diana Nur; Mexitalia, Maria; Margawati, Ani; Noer, Etika Ratna; Andoyo, Robi; Hatimah, Ihat; Nuryanto, Nuryanto; Endrinikapoulos, Ariana (Poltekkes Kemenkes Bandung, 2024)
Stunting, characterized by impaired growth and development in children under five, is a major health issue caused by chronic malnutrition and recurrent infections during the first 1000 days of life. Protein intake is crucial for the provision of essential amino acids necessary for optimal growth and immune function. This study aimed to analyze the effect of whey protein-based high-protein biscuits on short-chain fatty acids (SCFA) levels in stunted children. A quasi-experimental design with a pre-post test group was used. Thirty-six stunted children were divided into two groups: the intervention group received whey protein-based high-protein biscuits, while the control group received an equivalent protein source from eggs and tempeh. SCFA levels were measured before and after the intervention. Paired T-tests and Wilcoxon tests were used for statistical analysis. The study found that high-protein biscuits significantly increased SCFA levels (acetate, propionate, and butyrate) in the intervention group (p-value < 0.001). These findings suggest that high-protein biscuits can positively influence gut microbiota and overall health in stunted children. High-protein biscuits can effectively increase SCFA levels in stunted children, contributing to improved gut health. Future studies should explore the long-term effects and potential risks associated with this intervention